2023
DOI: 10.7196/samj.2023.v113i2.431
|View full text |Cite
|
Sign up to set email alerts
|

Loadshedding and Healthcare: Salt in The Wound?

Abstract: Loadshedding and healthcare: Salt in the wound?To the Editor: South Africa (SA)'s energy crisis is a longstanding problem. With no permanent solution in sight, the worsening power cuts continue to detrimentally impact the quality of public healthcare across the nation. [1,2] At present, the country is experiencing the highest numbers of loadshedding hours since its inceptionaveraging over 1 500 hours in 2022. [3] As the effects of the COVID-19 pandemic remain apparent, it is questionable whether we can handle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Another challenge was that nationally scheduled power cuts (loadshedding) negatively influenced participants' Wi-Fi access resulting in long download times. Challenges because of loadshedding have also been reported by various authors who confirmed that the continuous loadshedding in South Africa has a huge impact on healthcare, including the use of mHealth tools (Githaiga et al 2023;Malange 2023;Romski et al 2023).…”
Section: Social Determinants Of Healthmentioning
confidence: 71%
“…Another challenge was that nationally scheduled power cuts (loadshedding) negatively influenced participants' Wi-Fi access resulting in long download times. Challenges because of loadshedding have also been reported by various authors who confirmed that the continuous loadshedding in South Africa has a huge impact on healthcare, including the use of mHealth tools (Githaiga et al 2023;Malange 2023;Romski et al 2023).…”
Section: Social Determinants Of Healthmentioning
confidence: 71%
“…South Africa has grappled with an energy crisis, marked by persistent rolling electricity blackouts or load shedding since 2007. The current situation reflects the highest recorded load shedding hours, averaging over 1500 h since its inception [12]. ESKOM (Electricity Supply Commission) remains the exclusive electricity supplier, and challenges in power supply are anticipated to persist [13].…”
Section: Discussionmentioning
confidence: 99%
“…South Africa is in an energy crisis and has been experiencing rolling electricity blackouts, otherwise known as load shedding, since 2007. The country is currently experiencing the highest load shedding hours averaging over 1500 hours since its inception 10 . Currently, ESKOM is the sole supplier of electricity in South Africa, and the power supply struggles are envisaged to persist 11 .…”
Section: Discussionmentioning
confidence: 99%